Virtual managers' perspective on adoption of new work forms - case of Estonian service sector / Gerda Mihhailova - Gerda, Mihhailova (Universiti Teknologi MARA Cawangan Sarawak, 2017)
ICTs have changed the way people interact with each other - not only in everyday situations, but also in the work context. Inevitably, managers need to develop their management techniques to suit the new ICT-mediated communication reality. As it has been suggested that new flexible work forms (virtual work, distance work) are more suitable for service organisations, the current paper aims to better understand new managerial practices used by virtual service managers and aspects that hinder the widespread use of new work forms. Thirty six service managers representing all twelve subsectors of the Estonian service industry were interviewed. Results indicate that flexible work forms, namely virtual work, is used more extensively than distance work. As the general knowledge level of new work forms and suitable management techniques is low, joint efforts of different societal interest groups are needed in order to raise awareness of new work forms.